Kunitz trypsin inhibitor in addition to Bowman-Birk inhibitor influence stability of lunasin against pepsin-pancreatin hydrolysis. (December 2016) - Price, Samuel J.; Pangloli, Philipus; Krishnan, Hari B.; Dia, Vermont P.
Abstract: Soybean contains several biologically active components and one of this belongs to the bioactive peptide group. The objectives of this study were to produce different lunasin-enriched preparations (LEP) and determine the effect of Bowman-Birk inhibitor (BBI) and Kunitz trypsin inhibitor (KTI) concentrations on the stability of lunasin against pepsin-pancreatin hydrolysis (PPH). In addition, the effect of KTI mutation on lunasin stability against PPH was determined. LEP were produced by calcium and pH precipitation methods of 30% aqueous ethanol extract from defatted soybean flour. LEP, lunasin-enriched commercially available products and KTI control and mutant flours underwent PPH and samples were taken after pepsin and pepsin-pancreatin hydrolysis. The concentrations of BBI, KTI, and lunasin all decreased after hydrolysis, but they had varying results. BBI concentration ranged from 167.5 to 655.8 μg/g pre-hydrolysis and 171.5 to 250.1 μg/g after hydrolysis. KTI concentrations ranged from 0.3 to 122.3 μg/g pre-hydrolysis and 9.0 to 18.7 μg/g after hydrolysis. Lunasin concentrations ranged from 8.5 to 71.0 μg/g pre-hydrolysis and 4.0 to 13.2 μg/g after hydrolysis. In all products tested, lunasin concentration after PPH significantly correlated with BBI and KTI concentrations. Mutation in two KTI isoforms led to a lower concentration of lunasin after PPH. This is the first report on the potential role of KTI in lunasin stability against PPH and must be considered in designing lunasin-enriched products that could potentially survive digestion after oral ingestion. Graphical abstract: Highlights: Lunasin-enriched samples were produced by calcium and pH precipitation methods. KTI affected lunasin stability against PPH. BBI and KTI correlated with the percentage residual lunasin after PPH. Bioactive peptides in lab-LEP are higher than commercially available LEP.